Influence of the Titania Content on the Microstructure and Properties of Plasma Sprayed Alumina-Titania Coatings - Anna Goral; Wojciech Zorawski; Otakar Bokuvka (Communications - Scientific letters of the University of Zilina, 2018)
The composite alumina-titania coatings have been widely used in industry fields to protect metallic components from wear, corrosion and thereby prolonging their service time. This paper presents an analysis of the microstructure and mechanical properties of Al2O3-TiO2 composite coatings, plasma sprayed on steel substrates from feedstocks containing various concentrations of the TiO2 powder. The coatings revealed lamellar microstructure, formed by the rapid solidification of molten droplets of the powder on previously deposited splats. The main phase identified in the coatings was γ-Al2O3 phase, the others were TiO2 and α-Al2O3, as well as amorphous phase. The results indicated significant improvement of hardness, Young’s modulus and fracture resistance of coatings with an increase in TiO2 from 3 wt. % to 13 wt. %. The friction coefficient was found to be the same for both coatings.